ANALISIS EFISIENSI DAN FAKTOR YANG MEMENGARUHI PILIHAN SALURAN PEMASARAN - Rizka Karlina Putri; Rita Nurmalina; Burhanuddin Burhanuddin (Universitas Mercu Buana, 2018)
Abstract. This research is intended to analyze the efficiency and the factors influencing the choice of marketing of vanda douglas cutting orchids in Bogor district. Respondentsin this study requires 40 farmers vanda douglas cutting orchids. The analysis ofmarketing channel efficiency uses marketing margins, farmers' share and profit-to-costratio. The result of this research is there are three patterns of marketing channel ofVanda douglas cutting orchids: (1) farmers - village collector traders - wholesalers -consumers (2) farmers - wholesalers - consumers (3) farmers - florists - consumers.Seen from the efficiency of the most efficient marketing channel is on channel two thatis farmers - wholesalers - consumers. Where on this channel has a low margin of 72percent, farmer shares by 28 percent and the ratio of profit to the largest cost of 7.4. Ofthe seven factors that affect the quality of work. Vanda douglas hence significantexplanatory variable to response variable is farmer age, orchid sale price, long farmingand land area.